Blood oxygen level-dependent and perfusion magnetic resonance imaging: detecting differences in oxygen bioavailability and blood flow in transplanted kidneys - Sadowski, Elizabeth A.; Djamali, Arjang; Wentland, Andrew L.; Muehrer, Rebecca; Becker, Bryan N.; Grist, Thomas M.; Fain, Sean B. (Magnetic resonance imaging, 2010)
Functional magnetic resonance imaging (fMRI) is a powerful tool for examining kidney function, including organ blood flow and oxygen bioavailability. We have used contrast enhanced perfusion and blood oxygen level-dependent (BOLD) MRI to assess kidney transplants with normal function, acute tubular necrosis (ATN) and acute rejection. BOLD and MR-perfusion imaging were performed on 17 subjects with recently transplanted kidneys. There was a significant difference between medullary R2⁎ values in the group with acute rejection (R2⁎=16.2/s) compared to allografts with ATN (R2⁎=19.8/s; P=.047) and normal-functioning allografts (R2⁎=24.3/s;P=.0003). There was a significant difference between medullary perfusion measurements in the group with acute rejection (124.4±41.1 ml/100 g per minute) compared to those in patients with ATN (246.9±123.5 ml/100 g per minute; P=.02) and normal-functioning allografts (220.8±95.8 ml/100 g per minute; P=.02). This study highlights the utility of combining perfusion and BOLD MRI to assess renal function. We have demonstrated a decrease in medullary R2⁎ (decrease deoxyhemoglobin) on BOLD MRI and a decrease in medullary blood flow by MR perfusion imaging in those allografts with acute rejection, which indicates an increase in medullary oxygen bioavailability in allografts with rejection, despite a decrease in blood flow.